2002
DOI: 10.1038/ni811
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of IgE Fc reveals an asymmetrically bent conformation

Abstract: The distinguishing structural feature of immunoglobulin E (IgE), the antibody responsible for allergic hypersensitivity, is the C epsilon 2 domain pair that replaces the hinge region of IgG. The crystal structure of the IgE Fc (constant fragment) at a 2.6-A resolution has revealed these domains. They display a distinctive, disulfide-linked Ig domain interface and are folded back asymmetrically onto the C epsilon 3 and C epsilon 4 domains, which causes an acute bend in the IgE molecule. The structure implies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
183
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(190 citation statements)
references
References 48 publications
5
183
1
1
Order By: Relevance
“…S1 A). However, it is unexpected here since the C 2-C 2 interaction is actually predominantly polar (19), and so the non-polar character in the C 2-C 2 association is not a trivial consequence of the equivalence of the corresponding residues in the contact region. In addition, there were three salt bridges identified within the C 2-C 3,4 interface (19) and (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…S1 A). However, it is unexpected here since the C 2-C 2 interaction is actually predominantly polar (19), and so the non-polar character in the C 2-C 2 association is not a trivial consequence of the equivalence of the corresponding residues in the contact region. In addition, there were three salt bridges identified within the C 2-C 3,4 interface (19) and (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…However, subsequent fluorescence data of the homologous IgE molecule in solution seemed to indicate that the IgE Fc was actually sharply bent (18). These initial observations were then clearly detailed when the crystallographic structure of the IgE Fc was solved (19), showing that the C 2 domains are bent back toward the C 4 domains by Ϸ60°. These findings raise the possibility that the homologous IgM Fc region may also be bent, although it is not immediately obvious whether such a bent structure could possibly be assembled into a pentameric complex that is planar and in which all of the known disulfide bridges both within and between monomers are satisfied (20).…”
mentioning
confidence: 98%
“…Flexibility in the Cε3-Cε4 interdomain angle has been welldocumented through studies of unliganded Fcε3-4 structures in different crystal forms (26,27), as well as the unliganded IgE-Fc structure (28) and the sFcεRIα complexes with both Fcε3-4 and IgE-Fc (20,21). Among all of these structures the interdomain angle varies over a range of ∼25°between the most "open" (in the sFcεRIα complexes) and the most "closed" (chain D in the derCD23 complex reported here) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we report the crystal structure of the antibody adalimumab Fab with the EFab domain substitution. In comparison with the previously reported adalimumab Fab and IgE Fc structures, 18,19 the adalimumab EFab shows a high degree of similarity in the variable domains. However, clear differences in the relative domain orientation of variable domains with respect to constant domains are observed that do not appear to have a detrimental effect on target antigen binding.…”
Section: Introductionmentioning
confidence: 47%